The non-invasive assessment of the sphenoid sinus: a review - Munjal, Manish; Sethi, Suneet; Vohra, Hitant; Munjal, Shubham; Prabhakar, Anu; Garg, Seema; Pooni, Navreen; Gill, Angad Singh; Dhillon, Karan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The sphenoid sinus with its peculiar mucociliary drainage effected by pathology at the spheno-ethmoidal recess necessitates an intervention, medical or surgical. Role of basic imaging in pre-treatment evaluation is elaborated upon.